Cerebrospinal fluid findings in reversible cerebral vasoconstriction syndrome: a way to differentiate from cerebral vasculitis? - Kraayvanger, L. (Clin Exp Immunol, 2018)
Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by an acute onset of severe headache and multi‐focal segmental vasoconstriction of cerebral arteries resolving within 12 weeks. Diagnostic criteria include normal or near‐normal findings in cerebrospinal fluid (CSF) analysis, especially leucocyte levels < 10/mm³. Distinguishing RCVS from primary angiitis of the central nervous system (PACNS) is essential to avoid unnecessary and sometimes unfavourable immunosuppressive treatment. We reviewed retrospectively the clinical and diagnostic data of 10 RCVS patients who presented in our neurological department from 1 January 2013 to February 2017. The main purpose was to verify whether CSF leucocyte counts < 10/mm³ serve to discriminate RCVS from PACNS. Five of six patients who underwent lumbar puncture presented with CSF leucocyte levels ≥ 10/mm³. Two patients had a history of misinterpretation of CSF pleocytosis as cerebral vasculitis and of immunosuppressive treatment. A complete restitution of cerebral vasoconstriction was evident in all. No patient had further cerebral strokes or bleedings without immunosuppressive treatment over more than 12 weeks. Despite the established diagnostic criteria, RCVS can manifest with CSF leucocyte levels > 10/mm³. Careful anamnesis and the response of ‘vasculitis‐like angiography’ to nimodipine given as a test during angiography and as oral medication are key to differentiate RCVS from cerebral vasculitis.